Increasing Student Learning Outcomes In Environmental Pollution Learning Material By Utilizing Waste as a Hidden Curriculum - Nopia, Sri; Juanda, Anda; Gloria, Ria Yulia (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2022)
This study aims to explain student learning activities and compare the learning outcomes of experimental and control classes on environmental pollution materials. The study was carried out at SMA N 1 Plumbon classes X MIPA 1 and X MIPA 2. This study's research design is an experimental design of this design in the form of a Pretest-Posttest Control Group Design. The data for this study was gathered through observations and tests. Because of the high category, the findings showed increased student learning activities, with an average score of 70.72%. There were substantial variations in student learning results in the experimental class, which used waste as a hidden curriculum and obtained an average score of N-Gain of 0.51 medium criteria, compared to the control class, which obtained an average score of N-Gain of 0.28 low criteria. The obtained significance value was 0.030, which is lower than 0.05, it is conclude that using waste as a hidden curriculum can increase student learning outcomes and activities.ABSTRAK: Penelitian ini bertujuan untuk mendeskripsikan aktivitas belajar siswa dan menganalisis perbedaan hasil belajar siswa kelas eksperimen dengan kelas kontrol pada materi pencemaran lingkungan. Penelitian dilakukan di SMA N 1 Plumbon kelas X MIPA 1 dan X MIPA 2. Desain penelitian yang digunakan dalam penelitian ini adalah experimental design desain ini dalam bentuk Pretest-Posttest Control Group Design. Penelitian ini menggunakan observasi dan tes sebagai metode pengumpulan data. Hasil penelitian menunjukan peningkatan aktivitas pembelajaran siswa, dengan nilai rata-rata 70,72% berkategori tinggi. Terdapat perbedaan hasil belajar siswa yang signifikan pada siswa kelas eksperimen yang menerapkan pembelajaran dengan pemanfaatan sampah sebagai hidden curriculum diperoleh nilai rata-rata N-Gain 0,51 kriteria sedang, dengan kelas kontrol nilai rata-rata N-Gain 0,28 kriteria rendah. Nilai signifikansi yang diperoleh 0,030<0,05, disimpulkan bahwa penerapan pemanfaatan sampah sebagai hidden curriculum dapat meningkatkan hasil belajar siswa dan aktivitas belajar siswa.